2016
DOI: 10.1016/j.na.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

On the Cauchy problem for non-local Ornstein–Uhlenbeck operators

Abstract: We study the Cauchy problem involving non-local Ornstein-Uhlenbeck operators in finite and infinite dimensions. We prove classical solvability without requiring that the Lévy measure corresponding to the large jumps part has a first finite moment. Moreover, we determine a core of regular functions which is invariant for the associated transition Markov semigroup. Such a core allows to characterize the marginal laws of the Ornstein-Uhlenbeck stochastic process as unique solutions to Fokker-Planck-Kolmogorov equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We note in passing that in principle [37] allows to handle anisotropic kernels, but precise upper estimate of the resulting heat kernel are non-trivial to obtain from the series representation given there. The reader interested in probabilistic methods may consult further results and references in [12,36,37,39,42,45].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…We note in passing that in principle [37] allows to handle anisotropic kernels, but precise upper estimate of the resulting heat kernel are non-trivial to obtain from the series representation given there. The reader interested in probabilistic methods may consult further results and references in [12,36,37,39,42,45].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In [5,Theorem 5.2], see also [39,Remark 5.11], it is shown that FC 2 A (X), under Hypothesis 2.1, is a core for the generator of P t in C b (X) equipped with the mixed topology. Recall that a core of an operator A : D(A) ⊆ X → X is a subspace C ⊆ D(A) which is dense in D(A) with respect to the graph norm…”
Section: Hypothesis 21 There Exists An Orthonormal Basis {Hmentioning
confidence: 99%
“…Proof. We point out that FC 2 A (X) is invariant with respect to P t (see [5,Theorem 5.2] and [39,Remark 5.11]), so to conclude we just need to show that FC 2 A (X) is contained in the domain of the generator L in L 2 (X, σ) and that it is dense in L 2 (X, σ).…”
Section: Invariant Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Although the Ornstein-Uhlenbeck R t is not a C 0 -semigroup on C b (H), we can define its generator (L, D(L)) by point-convergence topology (see, for instance, [9,12]) and its resolvent R(λ, L) of L is given by…”
Section: Lévy Ornstein-uhlenbeck Processesmentioning
confidence: 99%